Human‐Induced Pluripotent Stem Cell Culture Methods Under cGMP Conditions. (10th July 2020) - Rivera, Teresa; Zhao, Yuanyuan; Ni, Yuhui; Wang, Jiwu
Abstract: The discovery of induced pluripotent stem cells (iPSCs) revolutionized the approach to cell therapy in regenerative medicine. Reprogramming of somatic cells into an embryonic‐like pluripotent state provides an invaluable resource of patient‐specific cells of any lineage. Implementation of procedures and protocols adapted to current good manufacturing practice (cGMP) requirements is critical to ensure robust and consistent high‐quality iPSC manufacturing. The technology developed at Allele Biotechnology for iPSC generation under cGMP conditions is a powerful platform for derivation of pluripotent stem cells through a footprint‐free, feeder‐free, and xeno‐free reprogramming method. The cGMP process established by Allele Biotechnology entails fully cGMP compliant iPSC lines where the entire manufacturing process, from tissue collection, cell reprogramming, cell expansion, cell banking and quality control testing are adopted. Previously, we described in this series of publications how to create iPSCs using mRNA only, and how to do so under cGMP conditions. In this article, we describe in detail how to culture, examine and storage cGMP‐iPSCs using reagents, materials and equipment compliant with cGMP standards. © 2020 The Authors. Basic Protocol 1 : iPSC Dissociation Support Protocol 1 : Stem cell media Support Protocol 2 : ROCK inhibitor preparation Support Protocol 3 : Vitronectin coating Basic Protocol 2 : iPSC Cryopreservation Basic Protocol 3 : iPSC Thawing